u+u+3=u+46

Simple and best practice solution for u+u+3=u+46 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for u+u+3=u+46 equation:


Simplifying
u + u + 3 = u + 46

Reorder the terms:
3 + u + u = u + 46

Combine like terms: u + u = 2u
3 + 2u = u + 46

Reorder the terms:
3 + 2u = 46 + u

Solving
3 + 2u = 46 + u

Solving for variable 'u'.

Move all terms containing u to the left, all other terms to the right.

Add '-1u' to each side of the equation.
3 + 2u + -1u = 46 + u + -1u

Combine like terms: 2u + -1u = 1u
3 + 1u = 46 + u + -1u

Combine like terms: u + -1u = 0
3 + 1u = 46 + 0
3 + 1u = 46

Add '-3' to each side of the equation.
3 + -3 + 1u = 46 + -3

Combine like terms: 3 + -3 = 0
0 + 1u = 46 + -3
1u = 46 + -3

Combine like terms: 46 + -3 = 43
1u = 43

Divide each side by '1'.
u = 43

Simplifying
u = 43

See similar equations:

| 3x-5(x-4)=-5+4x+13 | | 3x+9x-7=3(4x+4) | | 8t+40+16t-49=18t+23 | | 18x-12=3x^2 | | 7+6*2-2+8= | | 7a+21b=110 | | 2(1/6)*(3/26) | | d=85(4h) | | 34+32a-50=23a+26 | | 6x+6=6x+5 | | 2l+2w=98.2 | | 5-6y=35 | | -12720+200= | | 4/7x-1/3=1/5 | | 46.25/60= | | -11+x=-7x-8x+-8(-x+1) | | 7b+33+b+50=19b | | -7(-4x)=-4x+9 | | 6(2x-7)=3(5x-8) | | 8(y+8)=-4.3 | | -5c-4+7c=60 | | k[x]=6x+100k | | 9/x=11/7 | | 28+x(21)=35 | | 2x-32=5x+1 | | 1=k*5 | | 4x-2x-76=3x+11 | | 2(3x-4x+1)=8x | | 7/12a=13/14 | | 3k/287=2/3 | | -4x-4x=-7x+6 | | 4=2-36 |

Equations solver categories